Offshoring of white-collar services : Business and economic perspective - Artur Klimek (Offshoring of white-collar services : Business and economic perspective, 2020)
This is one of the few books on the market dealing with offshoring of professional services, a dynamic phenomenon of high relevance in the global economy. The market for offshore services is worth more than 1 trillion dollars annually and employs millions of people. Global offshoring of services has been recently undergoing a profound transformation due to automation and robotisation of tasks. It can be associated with the increased codifi cation of knowledge, commoditisation of services and advancement in technology. The global perspective has been supplemented by a detailed analysis of offshoring in Central and Eastern Europe. It witnesses a dynamic growth of foreign direct investment (FDI) in professional services, resulting in capital and knowledge transfers. This books is a result of a holistic approach and an interdisciplinary research. It is enriched with conclusions from meetings with representatives of: authorities responsible for attracting FDI; associations of offshoring fi rms; and enterprises operating in professional services. It was also a result of numerous discussions with scholars during academic conferences and research seminars
10.1515/9783110690668; 10.1515/9783110690668